Case report: Significant lesion reduction and neural structural changes following ibogaine treatments for multiple sclerosis - Chen, David Qixiang; Inzunza Domínguez, José Adalberto; Valle Uzeta, Juan Manuel; Pushparaj, Abhiram P.; Dickinson, Jonathan E. (Frontiers in Immunology, 2025)
Multiple sclerosis (MS) is a debilitating neurodegenerative disease characterized by demyelination and neuronal loss. Traditional therapies often fail to halt disease progression or reverse neurological deficits. Ibogaine, a psychoactive alkaloid, has been proposed as a potential neuroregenerative agent due to its multifaceted pharmacological profile. We present two case studies of MS patients who underwent a novel ibogaine treatment, highlighting significant neuroimaging changes and clinical improvements. Patient A demonstrated substantial lesion shrinkage and decreased Apparent Diffusion Coefficient (ADC) values, suggesting remyelination and reduced inflammation. Both patients exhibited cortical and subcortical alterations, particularly in regions associated with pain and emotional processing. These findings suggest that ibogaine may promote neuroplasticity and modulate neurocircuitry involved in MS pathology.